2014
DOI: 10.3233/bmr-130424
|View full text |Cite
|
Sign up to set email alerts
|

An effective coaching intervention for people with low recovery expectations and low back pain: A content analysis

Abstract: This effective health coaching intervention for people with non-chronic NSLBP and low recovery expectation concentrated on goal setting and action planning and addressed the essential factors of recovery expectations. This study suggests that coaching interventions are likely to be different in this population compared to similar interventions in chronic conditions due to pre-existing levels of readiness to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Validated measures are now available to gauge this risk factor of poor RTW and/or recovery [ 37 , 39 , 48 ]. Investing in interventions such as education, coaching or multidisciplinary programs could improve RTW rates by adjusting expectations; thereby reducing the associated costs of lost productivity [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Validated measures are now available to gauge this risk factor of poor RTW and/or recovery [ 37 , 39 , 48 ]. Investing in interventions such as education, coaching or multidisciplinary programs could improve RTW rates by adjusting expectations; thereby reducing the associated costs of lost productivity [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, findings from this study support the expanding pool of evidence demonstrating quantifiable benefits of cognitive behavioral interventions for chronic pain management ( Hajihasani et al, 2019 ;Cherkin et al, 2017Cherkin et al, , 2016Kamper et al, 2015 ;Carpenter et al, 2012 ;Hoffman et al, 2007 ) and digital interventions for managing chronic pain conditions ( Toelle et al, 2019;Amorim et al, 2019;Hüppe et al, 2019;Mecklenburg et al, 2018;Huber et al, 2017;Buhrman et al, 2016;Iles et al, 2014;Beatty & Lambert, 2013;Lawson et al, 2013 ;Buhrman et al, 2004 ). These methods of pain management could also potentially mitigate the use of more expensive and invasive types of care that may pose greater risk of harm to the patient ( Cherkin et al, 2018 ;Herman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 52%
“…Conservative approaches, such as exercise and manual therapy (e.g., spinal manipulation), have been widely regarded as first-line treatments to improve pain and function for individuals with LBP. Overall healthcare costs are reduced and prognosis is typically improved when services from providers of conservative interventions, such as physical therapists (PTs) and chiropractors, are used by patients within a few weeks of LBP symptom onset ( Carey et al, 2019;Kazis et al, 2019;Carvalho et al, 2017;Gay et al, 2016;Iles et al, 2014;Kosloff et al, 2013;Nelson et al, 2005 ;Legorreta et al, 2004 ). However, long-term recovery is not always sustained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited research on the use of MI by physiotherapists, although studies investigating other motivational interventions have demonstrated that their implementation may: increase patient self-efficacy and activity levels (McGrane et al, 2015); address recovery expectations (Iles et al, 2014); enhance outcome expectancy and working alliance (Cheing et al, 2014); and increase patient motivation, exercise, compliance and physical function (Vong et al, 2011).…”
Section: Motivational Interviewing As a Psychologically Informed Approachmentioning
confidence: 99%